Changes in Touch Avoidance, Stress, and Anxiety During the COVID-19 Pandemic in Italy - Passarelli, Marcello; Casetta, Laura; Rizzi, Luca; Perrella, Raffaella; Maniaci, Giuseppe; La Barbera, Daniele (Frontiers in Psychology, 2022)
In the present study we analyzed how attitudes towards touch have changed during the COVID-19 pandemic in an Italian sample, through two different studies: in the first we contacted participants of the Italian validation study of the Touch Avoidance Questionnaire, asking them to take part in a follow-up study (N=31, 64.5% women, age 42.58 ± 15.15); in the second we recruited a new sample of 717 people (73.92% women, age 34.25 ± 13.11), comparing it to the full validation sample of the Touch Avoidance Questionnaire (N=335, 64.48% women, age = 35.82 ± 14.32) to further investigate the relationship between the pandemic, stress responses, fear of contagion, anxiety, and attitudes towards touch. Overall, we found higher post-pandemic scores for touch avoidance towards strangers and family members and lower scores in touch avoidance towards friends of either gender, along with a slight increase in anxiety and stress. Touch avoidance was also positively related to anxiety and/or stress levels except for touch avoidance towards same-sex friends, for which the relationship with anxiety was negative. Surprisingly, we found that young people were the most anxious, despite older people being more at-risk of dying from Covid-19. Women were slightly more stressed out. Covid-19-related fears were significant predictors of touch avoidance towards partners, friends and strangers, but not of touch avoidance towards family. The results suggest that touch avoidance increased during the pandemic (except towards same-sex friends), together with anxiety and stress levels, but the change was relatively small.